OUTCOME OF USE OF 1% SILVER NITRATE IN PATIENTS WITH LOW LYING PERIANAL FISTULA - Iqbal, Abdullah; Ahmed, Tanweer; Khan, Imran; Perveen, Sughra; Khan, Muhammad Iqbal (Journal of Ayub Medical College Abbottabad, 2019)
Background: Anorectal fistula is a common illness which is seen among the middle-aged male patients. Various surgical procedures have been proposed and are associated with the recurrence of the fistula, repeated surgery and in some cases incontinence which may reach up to 43% in complicated fistulas. The purpose of this study was to assess and formulate a non-surgical procedure for fistula in ano through irrigation of the fistula tract with 1% of silver nitrate solution in healing the low perianal fistula. Methods: Seventy-nine patients presenting to the outpatient department of Ward 3, Surgical unit 1 in Jinnah Postgraduate Medical Centre during a period of 8 months from April to November 2017 with complain of perianal pain and pussy discharge were included in the study. Three patients of the total 79 patients lost to follow up. Outcome measure were cessation of the symptoms for consecutive 10 weeks. Results: Seventy-six patients were assessed and underwent irrigation using this 1% of silver nitrate solution. Out of 76 patients, 58 (76.3%) patients showed complete clinical healing while 18 (23.68%) of patients showed failure to clinical healing. Patients with continuous discharge had a significantly higher rate of complete clinical healing than those with intermittent discharge. Conclusion: From this study it can be concluded that cauterizing and corrosive properties of silver nitrate are effective in treating the patients with low lying perianal fistula. We suggest that this method should be used as a first line treatment option for all the patients presenting with low lying anal fistula since it is simple, can be easily performed on an OPD basis is minimally invasive and avoids any complication. Keywords: silver nitrate; perianal fistula; low lying perianal fistula; nonoperative management